Politik Sengketa Batas Wilayah (Kota Kupang dan Kabupaten Kupang) - Stefanus Triadmaja; Nur Hidayat Sardini (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This study is to analyze the impact of Political Border Disputes in the City of Kupang and Kupang Regency. Regional boundary disputes that occurred in the Nasipanaf region began since the enactment of Law Number 5 of 1996 Establishment of the Kupang Second Level Regional Municipality. on April 25, but the territorial borders were not taken seriously by the Government. The physical boundary between Kupang City and Kupang Regency on the ground is that there are still unclear boundary points, especially in the Nasipanaf region between Kelurahan Penfui and Desa Baumata Barat which have not been agreed between the two parties. The method used in this research is a qualitative descriptive method based on case studies as the sample in this study there are people from both the research locus and the government as the authorized party for decision making. The findings obtained in this study indicate that there has been a clash between residents resulting in conflict over the past few years. In addition, administrative issues also become a problem for people who are in the border area and infrastructure development also influence in the dispute over this area.